2010
DOI: 10.1175/2010jas3457.1
|View full text |Cite
|
Sign up to set email alerts
|

A Nonlinear Impedance Relation for the Surface Winds in Pressure Disturbances

Abstract: The ''impedance relation'' between the wind perturbation within an ageostrophic atmospheric disturbance and its pressure perturbation and intrinsic propagation speed has been in use for decades. The correlation between wind and pressure perturbation was established through this relation. However, a simple Lagrangian model of an air parcel traversing an idealized sinusoidal wave in the pressure field indicates that the impedance relation produces significant errors. Examination of the nonlinearized horizontal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The relatively long period of these waves suggests that the origin is not local. Neglecting Coriolis forces and assuming a linear relationship between wind and pressure perturbations at the first order (Banfield et al., 2020; Coleman & Knupp, 2010), the phase speed, c , can be computed by c = u + Pʹ /( ρ · uʹ ), where u is the wind speed, ρ is the atmospheric density, and Pʹ and uʹ are the pressure and wind perturbations, respectively. It leads to phase speeds of 26–28 ms −1 and horizontal wavelengths of 70–90 km.…”
Section: Effects Of the My36/2022a Regional Dust Storm On The Surface...mentioning
confidence: 99%
“…The relatively long period of these waves suggests that the origin is not local. Neglecting Coriolis forces and assuming a linear relationship between wind and pressure perturbations at the first order (Banfield et al., 2020; Coleman & Knupp, 2010), the phase speed, c , can be computed by c = u + Pʹ /( ρ · uʹ ), where u is the wind speed, ρ is the atmospheric density, and Pʹ and uʹ are the pressure and wind perturbations, respectively. It leads to phase speeds of 26–28 ms −1 and horizontal wavelengths of 70–90 km.…”
Section: Effects Of the My36/2022a Regional Dust Storm On The Surface...mentioning
confidence: 99%
“…While many of the phenomena mentioned above tend to occur largely unnoticed, large-amplitude gravity waves, wake lows, and other mesoscale convective systems (MCSs) leading to severe weather have received much attention during recent decades (Ramamurthy et al 1993;Coleman and Knupp 2009;Coleman and Knupp 2010;Adams-Selin and Johnson 2013). A mix of microbarograph traces and pressure observations at hourly or longer intervals have been the most common tools available to study such events (Bosart et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The wake low was propagating toward the southeast (from 3108) at 16 m s 21 . Since the perturbation winds in a wake low are in the opposite direction of the wake low propagation, ambient easterly low-level winds (also opposite of the propagation direction) enhanced the net winds in the wake low (e.g., Coleman and Knupp 2009).…”
Section: A 13 April 2009mentioning
confidence: 99%
“…3a, the lower levels of the atmosphere were rather stable, with average N between 0.015 and 0.020 s 21 , but slightly less stable air was located above 1500 m MSL. Coleman (2008) showed that, for any vertical displacements above a point in the atmosphere, where p9 is the pressure perturbation at height z, N is the Brunt-Vä isä lä frequency fN5[(g/u)(du/dz)] 1/2 g, r 0 is the unperturbed density at each z, and dz is the vertical displacement at each height. Therefore, for a given vertical displacement, the pressure perturbation below it will have larger magnitude when the static stability is higher, consistent with the discussion in section 1.…”
Section: A 13 April 2009mentioning
confidence: 99%
See 1 more Smart Citation